Konsep Hati Menurut Robert Frager Analisis Buku Psikologi Sufi - Sivah Vahmi; Muhammad Noupal; Erika Septiana (CV. ITTC INDONESIA, 2025)
This study aims to analyze the concept of the heart (qalb) in the perspective of Robert Frager as explained in his work Sufi Psychology: For the Transformation of Heart, Soul, and Spirit. Frager, a transpersonal psychologist and modern Sufi, harmoniously integrates Western psychological approaches with Islamic spiritual values. The research employs a qualitative method with a library research approach through the collection, examination, and analysis of various relevant sources. The findings indicate that Frager views the heart as the spiritual center of human existence, functioning as a bridge between the self and the soul, as well as the core of inner awareness that guides human behavior. The heart serves as a vessel of divine love, wisdom, and light that shapes one’s spiritual consciousness and moral awareness. The purification of the heart through spiritual disciplines such as dhikr (remembrance of God), muhasabah (self-reflection), fasting, and self-control leads individuals toward physical, psychological, and spiritual harmony. Frager’s thought contributes significantly to the development of modern Sufi psychology that emphasizes inner healing, spiritual development, and self-transformation. His perspective provides a holistic understanding of human existence by integrating spiritual and psychological dimensions, helping modern individuals achieve serenity, self-awareness, and closeness to God in a materialistic and fast-paced world.